Pengaruh Efikasi Diri Terhadap Keberhasilan Usaha (Studi Pada Program Mahasiswa Wirausaha (PMW) Universitas Jambi) - Tia Maryadi (Jurnal Dinamika Manajemen, 2021)
This research entitled the influence of self-efficacy on business’s success (study on PMW Universitas Jambi students). This research’s objectives are to determine the influence of self-efficacy on business’s success both simultaneously and partially in 2019 PMW Universitas Jambi. The sampling techniques used in this study was purposive sampling by the representatives of 2019 PMW Universitas Jambi students that counted 60 samples. Analysis techniques used in this study were descriptive statistics and multiple regression using SPSS 23. The results of this research are simultaneously, self-efficacy influence the business’s success, while partially only creative and managing finance variable were influence business’s success.